Respuestas

  • Usuario de Brainly
2015-09-15T03:46:10+02:00
A) (5+b)(25 - 5a +a^2) = [(5*25) -(5*5a)+ (5*a^2) +(b*25)-(b*5a)+(b*a^2)]
[125- 25a+5a^2+25b-5ba+ ba^2  ]   =    [ba^2+5a^2-5ba-25a+25b+125]

b)(x-3)(x^2 +3x +9) = [(x*x^2)+(x*3x)+(x*9)-(3*x^2)-(3*3x)-(3*9)]
[x^3+3x^2+9x-3x^2-9x-27]     = [ x^3-27]

c) (b+2)(b^2-2b+4) = [(b*b^2)-(b*2b)+(b*4)+(2*b^2)-(2*2b)+(2*4)]
[b^3 -2b^2+4b+2b^2-4b+8]   = [b^3+8]

d)(5+z) ^3  = [ 5^3 + 3(5^2*z) +3(5 *z^2) + z^3] 
[125 + 75z+ 15z^2+z^3]

e)(c+3) (c+3) ^2 = (c+3) (c^2 +2(c*3)+3^2)  =  [(c*c^2)+(c*6c)+(c*9)+(3*c^2)+(3*6c)+(3*9)]    = [c^3+6c^2+9c+3c^2+18c+27]   = c^3 +9c^2 +27c +27  = (c+3) ^3 

f)(3-c) ^3 =  [3^3 -3 (3^2 * c)+3(3*c^2)- c^3]
[27 -27c+9c^2-c^3]

saludos :)

90 4 90